(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate, based on scientific evidence, the action of hyaluronic acid in the treatment of wounds in patients with diabetic foot. An integrative literature review study was carried out using the following platforms: Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF), as a database. Online Medical Literature Search and Analysis System (MEDLINE). The descriptors were used: “Hyaluronic acid”, “Treatment”, “Wound healing”. In total, 685 articles were obtained, which after being submitted to the inclusion and exclusion criteria, 144 remained to evaluate the abstracts. After analyzing the abstracts, 10 articles were selected in the study. The results of the study showed that hyaluronic acid was shown to be quite effective in most of the selected articles, demonstrating rapid wound healing, increased tissue granulation and wound revitalization, improved blood supply to the wound site, keratinocyte production, reduction of some clinical signs such as: secretion, purulence, odor and exudate level, showing good water absorption capacity and complete cure rate. It is concluded that the use of AH in diabetic wounds is an important tool to minimize hospitalizations related to the condition of diabetes, reducing high rates of amputation of lower limbs, above all studies do not demonstrate severe contraindications or harmful effects that would lead to negative repercussions for its use, favoring healing and healing in a short period of time.